- #1

- 1

- 0

## Homework Statement

Solve for x

xln(x)-24+6ln(x)-4x=0

My attempt at the solution

I first moved "-24" and "-4x" to the right side of the equation yielding

xln(x)+6ln(x)=24+4x

I then converted the natural logarithms to exponent form and product form yielding

ln(x)^x+ln(x)^6 = 24+4x ====> ln(x^x*x^6)=24+4x =====> ln(x^(x+6))=24+4x

I then converted the equation in notation " e " form yielding

e^(24+4x)= x^(x+6)

Now I am stuck on where to proceed. I am aware that the answer has to be a positive number because the domain of a logarithm is always greater then 0.

Thanks